Hubungan Jenis Kb Suntik Dengan Produksi Asi Pada Ibu Menyusui 0-6 Bulan Di Wilayah Kerja Puskesmas - Utary Dwi Listiarini; Indah Dewi Sari; Ani Deswita Chaniago; Linda Juanti (MEJORA Medical Journal Awatara, 2026)
The success and achievement of breastfeeding are greatly influenced by several factors. One of the factors that can affect breast milk production is the use of contraceptives, namely the 3-month and 1-month contraceptive injections. The aim of this study was to determine the relationship between three-month and one-month injectable contraceptions with breast milk production in breastfeeding mothers aged 0-6 months in the working area of the Sajingan Besar Community Health Center, Sajingan Besar District, Sambas Regency, West Kalimantan Province in 2025. This study used a cross-sectiona designl. The study sample was 58 breastfeeding mothers who have babies aged 0-6 months. Data were analyzed using the Chi-square analysis test. The results of the study showed that the relationship between the use of injectable contraceptions had a significant relationship with the variable of breast milk production at a significance level of 0.001 (p<0.05). These results concluded that there was a relationship between the use of injectable contraceptions and breast milk production in breastfeeding mothers aged 0-6 months.